Self-Excitation System for Synchronous Generator - Zaleskis, Genadijs; Rankis, Ivars; Prieditis, Marcis (Electrical, Control and Communication Engineering, 2013)
Self-excitation for synchronous generator is described in the paper. The system is based on a buck converter input filter capacitor discharge through excitation winding of the generator. The buck converter is connected to the stator outputs through an uncontrollable diode rectifier, but excitation winding is used as a load. Input filter capacitor of the converter provides initial current pulse which magnetizes excitation system and produces the generator voltage increase, for this reason the capacitor is charged before self-excitation process starts.